Co-stressors chilling and high light increase photooxidative stress in diuron-treated red alga Kappaphycus alvarezii but with lower involvement of H2O2 - Reis, Marlos O.; Necchi, Orlando [UNESP]; Colepicolo, Pio; Barros, Marcelo P. (Academic Press Inc. Elsevier B.V., 2011)
Diuron is one of the most commonly found N-phenylurea herbicides in marine/estuarine waters that promotes toxic effects by inhibiting photosynthesis and affecting the production of reactive oxygen species (ROS) in autotrophs. Since photo- and thermoacclimation are also ROS-mediated processes, this work evaluates a hypothetical additive effect of high light (HL) and chilling (12 degrees C) on 50 nM diuron toxicity to the highly-photosynthetically active apices of the red alga Kappaphycus alvarezii. Additive inhibition of photosynthesis was mainly evidenced by significant decreases of quantum yield of photosystem II and electron transfer rates upon co-stressors exposure to diuron-treated algae. Under extreme 12 degrees C/HL/diuron conditions, unexpected lower correlations between H2O2 concentrations in seawater and radical-sensitive protein thiols were concomitantly measured with the highest indexes of photoinhibition (parameter beta). Altogether, these data support the hypothesis that co-stressors chilling/HL additively inhibit photosynthesis in diuron-exposed K. alvarezii but with less involvement of H2O2 in injury effects than with only chilling or HL. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diuron; DCMU; Alga; Oxidative stress; Free radicals; Photosynthesis; Kappaphycus alvarezii; Hydrogen peroxide; Photoinhibition; PAM